Degree and Direction of Paid Employee/Volunteer Interchange in Nonprofit Organizations. Issue 4 (26th April 2013) - Chum, Antony; Mook, Laurie; Handy, Femida; Schugurensky, Daniel; Quarter, Jack
Abstract This study builds on an earlier one (Handy, Mook, and Quarter 2008) that examined the degree of interchangeability between volunteers and paid employees in nonprofit organizations. In the current study, we surveyed 836 nonprofits in Canada to understand what factors determine the degree of interchange between paid employees and volunteers, bearing in mind that this interchange can go in two directions: paid employees for volunteers and volunteers for paid employees. We found the degree of interchange to be widespread and in both directions. One of the most important predictors of the likelihood of interchange was the number of full‐time employees, suggesting that interchangeability occurs less frequently in organizations with a larger number of employees than in those with fewer employees. Religious congregations and organizations with workload increases were more likely to interchange tasks among volunteers and paid staff.